Adaptive approach of thermal comfort and correlation between experimental data and mathematical model in some schools and traditional buildings of Madagascar under natural ventilation. (August 2018) - Nematchoua, Modeste Kameni; Ricciardi, Paola; Buratti, Cinzia
Highlights: The traditional buildings are more comfortable than schools. Between 24 and 28 °C range, more than 80% of peoples were satisfied. Tsens was almost identical in schools and residences during rainy season. The thermal comfort range allows the selection of materials for micro-climate . Abstract: A good ventilation is important to improve indoor air in buildings. In Sub-Saharan Africa regions and other countries, both health and productivity are indeed elements depending on indoor comfort. The purpose of this research is to suggest a new thermal comfort approach based on subjective responses of occupants and mathematical models. There is a lack of data about indoor comfort in residential buildings in the tropical islands of Indian Ocean and the aim of the research is to propose guidelines for more comfortable constructions in Madagascar and other countries of the Indian Ocean. Experimental and subjective data were collected in 67 traditional habitats and 25 public and private schools, located in 25 districts of urban communes in the Northern Madagascar. Mathematical modelling was based on Rohles approach. At total of 992 questionnaires were collected and analysed during rainy and dry seasons. The results showed that traditional buildings were more comfortable than schools. Comfort temperature varied from 24.6 to 28.4 °C during both seasons in residences and schools. When the indoor air temperature varied in the 24.5–27.5 °C range, more than 80% of peoples were satisfied.